Political Communication Strategy of Single Candidate - Usrotul Afifah; Dedik Yoga Hermawan (Resolusi: Jurnal Sosial Politik, 2022)
Political communication strategy is very important in elections, both regional and national elections. Political communication strategies carried out by political parties or candidates include several things such as campaigns and collaboration with community groups. This was done to gain votes from the public. This study aims to determine the political communication strategy of a single candidate in the Wonosobo regional election. This research is qualitative research. The main subjects of this research are the main actors in the 2020 Wonosobo regional elections. The results show that a single candidate continues to carry out political communication strategies. The communication strategy is carried out in several ways including campaigning and also establishing cooperation with community groups. The campaigns carried out are generally in the form of installing banners or billboards, interviews with offline media and electronic media, and also visits to the public area. Meanwhile, collaborating with community groups is carried out by communicating between prospective leaders and group administrators, before finally withdrawing the votes of their members. This strategy success to bring the victory of single candidate on regional election in Wonosobo.